Implementasi Sistem Pemantauan Suhu Air Kolam Ikan Lele Berbasis IoT pada UMKM Budidaya Lele - Iwan Fitrianto Rahmad; M. Haidil Umam; Aditya Rizky Suryanta Sembiring; M. Irfan Fadillah; Muhammad Wahyu Pratama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Catfish cultivation requires good air quality, especially air temperature, because it affects the growth and health of the fish. One problem often faced by farmers is the manual process of monitoring pond water temperature, which is still less effective and efficient. This study aims to develop an automated Internet of Things (IoT)-based air quality monitoring system using ESP8266 and Arduino IoT Cloud. This system uses a DS18B20 sensor to measure temperature and a DHT11 sensor to measure the temperature and humidity of the air around the pond. Data is sent in real time via a WiFi network and displayed on the Arduino IoT Cloud dashboard. Data input is carried out automatically for 15 days at predetermined time intervals. The results show that the system is able to measure air temperature consistently and in real time with a temperature range between 25.5 °C and 31.1 °C, which is still within the tolerance limit for catfish. This indicates that the developed monitoring system can be used to continuously monitor pond environmental conditions. Therefore, this system can assist farmers in maintaining pond conditions remotely and support more accurate decision-making in catfish cultivation management. The main contribution of this research is the development of an IoT-based air quality monitoring system that is easy to implement, efficient, and suitable for application on an MSME scale.